Heat-resistant coating composition and preparation method thereof

By using the combination of rutile titanium dioxide with hollow glass microbeads, litho fibers and zircon sand in inorganic heat-resistant coatings, combined with the cross-linking and curing treatment of hexattitanate whiskers and potassium fluorosilicate, the problem of insufficient thermal conductivity and film formation performance of existing heat-resistant coatings is solved, and high thermal conductivity, good film formation and excellent weather resistance are achieved.

CN115418125BActive Publication Date: 2025-04-08HUNAN XIRUNFU POLYMER NEW MATERIAL CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211244672.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-12
Publication Date
2025-04-08
Estimated Expiration
2042-10-12

AI Technical Summary

Technical Problem

The existing inorganic heat-resistant coatings have shortcomings in thermal conductivity and coating mechanical strength, and it is difficult to meet the needs of high thermal conductivity and good film formation performance at the same time.

Method used

The thermally conductive fine aggregate based on rutile-type titanium dioxide is used, combined with hollow glass microbeads, litho fibers and zircon sand, and through specific ratios and processes, an inorganic heat-resistant coating with few oxygen vacancy and high thermal conductivity is formed. Hexatititanate whiskers and potassium fluorosilicate are used as crosslinking agents and curing agents to enhance the density and adhesion of the coating film.

Benefits of technology

High thermal conductivity, good film formation performance, excellent weather resistance and thermal expansion coefficient are achieved, which significantly improves the stability and heat resistance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 221012114413
    Figure 221012114413
  • Figure BDA0003886002060000051
    Figure BDA0003886002060000051
  • Figure BDA0003886002060000061
    Figure BDA0003886002060000061
Patent Text Reader

Abstract

The present invention discloses a heat-resistant coating composition, comprising the following components in parts by weight: 30-35 parts of fine aggregate, 2-10 parts of hexatitanate whiskers, 30-40 parts of film formers and 1-5 parts of curing agents; the film former is sodium silicate; the curing agent is potassium fluorosilicate; the fine aggregate is made of the following components in parts by weight: 35-45% of hollow glass microspheres, 5-20% of rock fiber and 2-10% of zircon sand and 100% of rutile titanium dioxide. The heat-resistant coating composition has outstanding advantages in terms of stability, heat resistance, water resistance and film-forming properties. The preparation method of the heat-resistant composition provided in the present application has good film quality and a thermal expansion coefficient of up to 1.0×10 ‑6 / ℃.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coatings, and in particular to a heat-resistant coating composition and a preparation method thereof. Background Art

[0002] Heat-resistant coatings can be divided into organic, inorganic and composite types based on their composition properties. Organic heat-resistant coatings usually refer to polymer compound coatings containing benzene rings such as polyimide, polyphenylene sulfide, polyether sulfone, and compound coatings containing corrosion-resistant elements such as organic fluorine, silicon or titanium. Inorganic high-temperature resistant coatings mainly include inorganic silicates, inorganic phosphates and silica sols. Composite heat-resistant coatings are usually made of inorganic and organic materials.

[0003] As one of the forms of titanium dioxide in nature, rutile has good light scattering and light reflection properties, high refractive index and non-toxic properties. It is chemically inert in both strong acid and strong alkaline environments, so it is considered to be the most stable thermodynamic material. The thermal conductivity of inorganic heat-resistant materials based on rutile titanium dioxide is related to the thickness of the film and the presence of oxygen vacancy defects in the film, and is usually used in combination with other inorganic thermal conductive materials.

[0004] In addition to the thermal conductivity of inorganic materials, the mechanical strength of inorganic heat-resistant coatings is also an important indicator of coating quality. Currently, inorganic materials usually use inorganic silicates and other components as film-forming agents to ensure the film-forming mechanical properties of the coating. Summary of the invention

[0005] In order to overcome the deficiencies of the prior art, one of the objects of the present invention is to provide a heat-resistant coating composition.

[0006] A second object of the present invention is to provide a method for preparing the heat-resistant coating composition.

[0007] One of the purposes of the present invention is achieved by the following technical solution:

[0008] A heat-resistant coating composition comprises the following components by weight: 30-35 parts of fine aggregate, 2-10 parts of hexatitanate whiskers, 30-40 parts of film formers and 1-5 parts of curing agents; the film formers are sodium silicate solutions; the curing agents are potassium fluorosilicate;

[0009] The fine aggregate is made of the following components by weight: 35-45% hollow glass microspheres, 5-20% rock fiber, 2-10% zircon sand and 100% rutile titanium dioxide;

[0010] The particle size of the rutile titanium dioxide is less than 200 nm, and the particle size of the hollow glass microspheres is less than 100 μm.

[0011] The heat-resistant coating composition is based on thermally conductive fine aggregate of rutile titanium dioxide, and is combined with hollow glass microspheres, rock fiber and zircon sand to obtain an inorganic heat-resistant coating with few oxygen vacancies, high thermal conductivity and compactness. Potassium hexatitanate whiskers are used as a cross-linking agent in combination with sodium silicate to assist in cross-linking, thereby making the coating film denser and more heat-resistant. Potassium fluorosilicate is used as a curing agent in combination with hexatitanate whiskers and sodium silicate to make the film more solid and have higher adhesion.

[0012] Furthermore, the fine aggregate is made of the following components in parts by weight: 35-40% of hollow glass microspheres, 10-15% of rock fiber, 4-6% of zircon sand and 100% of rutile titanium dioxide.

[0013] Furthermore, the fine aggregate is made of the following components in parts by weight: 35% of hollow glass microspheres, 10% of rock fiber, 5% of zircon sand and 45% of rutile titanium dioxide.

[0014] Furthermore, the modulus of the film-forming agent is 3-3.5.

[0015] Furthermore, the heat-resistant coating composition is made of the following components by weight: 30 parts of fine aggregate, 5 parts of hexatitanate whiskers, 35 parts of film-forming agent and 1.5-1.75 parts of potassium fluorosilicate; the film-forming agent has a modulus of 3 and is prepared into a 35% sodium silicate aqueous solution.

[0016] The second object of the present invention is achieved by adopting the following technical solution:

[0017] A method for preparing a heat-resistant coating composition comprises the following steps:

[0018] 1) Mix the fine aggregates evenly, add 30-40% by mass of the film-forming agent in water solution, and stir at high speed;

[0019] 2) adding an aqueous solution of a curing agent to the material of step 1), and adding hexatitanate whiskers while stirring at high speed;

[0020] 3) Add water to adjust the viscosity to 70-90 seconds for coating four cups;

[0021] 4) Apply to the carrier and dry at 110-130°C to a film thickness of 80-120 μm.

[0022] Furthermore, in step 4), drying is performed at 120° C. until the film thickness is 100-120 μm.

[0023] Furthermore, in step 1), the speed of high-speed stirring is 500 r / min, and the stirring time is greater than 30 min.

[0024] Furthermore, in step 4), the carrier is a common carbon steel plate, which is first degreased and derusted before coating.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The heat-resistant coating composition provided by the present application can obtain higher heat resistance, better adhesion to the substrate surface, better weather resistance and better thermal expansion coefficient by selecting inorganic fine aggregate, film-forming agent and curing agent with specific ratios and parameters, and can be coated on the substrate surface. The heat-resistant coating composition has outstanding advantages in stability, heat resistance, water resistance and film-forming property.

[0027] The preparation method of the heat-resistant composition provided in the present application has good film quality and the thermal expansion coefficient can reach 1.0×10 -6 / ℃. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Schematic diagram of calcination results under different curing agent dosages. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with specific implementation methods and drawings. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form a new embodiment.

[0030] The following are specific embodiments of the present invention. Unless otherwise specified, the raw materials, equipment, etc. used in the following embodiments can be obtained by purchase.

[0031] The following are the instruments and equipment used in the specific implementation of the present invention, including but not limited to the following:

[0032] XY200-2C electronic balance, Changzhou Lucky Electronic Equipment Co., Ltd.;

[0033] 101 electric heating blast drying oven, Beijing Yongguangming Medical Instrument Co., Ltd.;

[0034] SX-G03133 muffle furnace, Tianjin Zhonghuan Electric Furnace Co., Ltd.;

[0035] DW-2 force-enhancing stepless constant speed agitator, Gongyi Yuhua Instrument Co., Ltd.;

[0036] NO.1178 Tu-4 cup, Shanghai Hengping Instrument Factory;

[0037] QXD scraper fineness gauge, Tianjin Weida Testing Machine Factory, China;

[0038] ST9450A+ Multi-function Rapid Thermal Conductivity Tester, Xima Instruments;

[0039] AR932 film thickness meter, Xima Instruments;

[0040] DRE-Ⅲ infrared thermal imager, Xiangtan Xiangyi Instrument Co., Ltd.;

[0041] QYB pendulum type paint film hardness tester, Shenzhen Sanli Technology Co., Ltd.;

[0042] QCJ impact strength tester, Dalian Shengke Testing Instrument Co., Ltd.;

[0043] QFZ-Ⅱ paint film adhesion tester, Tianjin Material Testing Machine Factory, China;

[0044] J-2610 hanging alcohol blowtorch, Beijing Nanbei Chenyang Experimental Equipment Co., Ltd.

[0045] In the following specific examples, the rutile titanium dioxide used is commercially available industrial grade titanium dioxide, with a content of not less than 95% and a pH value of 9, and is ball-milled to a particle size of less than 200 nm before use.

[0046] The density of hollow glass beads used is 0.15g / cm 3 , particle size is less than 100μm.

[0047] The particle size of the rock fiber used is less than 125 μm; the fiber diameter is 1-8 μm; the zircon sand used has a hardness of 7.8, a specific gravity of 4.6-4.7, a melting point of 2340-2550°C, and a thermal expansion coefficient of 5×10 -6 / ℃.

[0048] In the following specific embodiments, the detection of high temperature resistance performance parameters is as follows:

[0049] The dried test piece obtained in the example was placed on a burning alcohol burner for baking, and the temperature of the back side of the test piece was tested every one minute using an infrared thermal imager.

[0050] In the following specific examples, the coating performance is tested as follows and a comprehensive score is given:

[0051] 1) Determine the coating adhesion according to GB / T 1720 "Determination of paint film adhesion", cm;

[0052] 2) Determine the coating viscosity according to GB / T 1723-79 "Determination of coating viscosity", s;

[0053] 3) Determine the coating hardness, Hv, according to GB / T 1730 "Determination of paint film hardness - Pendulum resistance test" standard;

[0054] 4) Determine the impact resistance of the coating according to GB / T 1732 "Determination of impact resistance of paint film", kg;

[0055] 5) Determine the coating thickness according to GB / T 1764-1979 "Determination of coating thickness", μm;

[0056] 6) The thermal expansion coefficient is obtained by the Hotdisc method.

[0057] Embodiment 1:

[0058] The heat-resistant coating composition of this embodiment has a formula composition as shown in the following table:

[0059] Table 1 Formula composition and coating properties of the heat-resistant coating composition of Example 1

[0060]

[0061]

[0062] Note 1): Sodium silicate has a modulus of 3 based on dry weight and is prepared into a 35wt% aqueous solution by adding water.

[0063] A method for preparing a heat-resistant coating composition comprises the following steps:

[0064] 1) Mix rutile titanium dioxide, hollow glass microspheres, rock fiber and zircon sand evenly, add 35wt% sodium silicate aqueous solution, and stir at high speed;

[0065] 2) Potassium hydrosilicate is added with 20 mL of water to prepare a potassium fluorosilicate aqueous solution, which is added to the material in step 1), and hexatitanate whiskers are added while stirring at high speed within 5 minutes to obtain a light gray colloid;

[0066] 3) Add water to the system and adjust the viscosity to 70-90 seconds for coating four cups;

[0067] 4) 100×100×10mm ordinary carbon steel plate, after degreasing and rust removal, is coated by brushing three times and dried according to the drying temperature and drying time shown in Table 1 until the film thickness reaches the corresponding film thickness.

[0068] From the comparison of coating properties of the heat-resistant coating compositions in Table 1, it can be seen that the thickness of the coating is positively correlated with the hardness of the coating; under the condition of equal weight portions of fine aggregate (comparison of Examples 1b and 1f with Comparative Example 1), as the content of potassium fluorosilicate decreases, the heat resistance of the coating decreases significantly; from the comparison of Examples 1d-1f with other Examples 1, it can be seen that when the fine aggregate consists of 13.5 parts of rutile silica, 12 parts of hollow glass microspheres, 3 parts of rock fiber and 1.5 parts of zircon sand, the comprehensive performance of the coating is better than that under other similar conditions.

[0069] Embodiment 2:

[0070] A heat-resistant coating composition is prepared from the following components by weight:

[0071] 13.5g of rutile titanium dioxide, 12g of hollow glass microspheres, 3g of rock fiber, 1.5g of zircon sand, 5g of hexatitanate whiskers, 35g of sodium silicate and 1.5g of potassium fluorosilicate are prepared; sodium silicate is prepared into a 35wt% aqueous solution; the modulus of sodium silicate is shown in Table 2 below: The surface drying time, whether it is burned through, and the temperature and thermal expansion coefficient after calcination for 5min of Example 2 are shown in the following table:

[0072] The preparation method of the heat-resistant coating composition comprises the following steps:

[0073] 1) Mix rutile titanium dioxide, hollow glass microspheres, rock fiber and zircon sand evenly, add a 35wt% film-forming agent aqueous solution, and stir at high speed;

[0074] 2) adding 20 mL of water to potassium fluorosilicate to prepare an aqueous solution, adding the potassium fluorosilicate aqueous solution to the material in step 1), and adding hexatitanate whiskers while stirring at high speed within 5 minutes to obtain a light gray colloid;

[0075] 3) Add water to the system and adjust the viscosity to 70-90 seconds for coating four cups;

[0076] 4) Apply the coating three times on a 100×100×10mm ordinary carbon steel plate, remove oil and rust, and dry at 120°C to a film thickness of 120μm.

[0077] Table 2 Formulation and partial heat resistance properties of the heat-resistant coating composition of Example 2

[0078]

[0079] As shown in Table 2, sodium silicate, as the main film-forming material, was burned through after calcination for 5 minutes when the modulus was 1-2, and when the modulus increased, the surface drying time also increased accordingly; when the modulus was 3, the thermal expansion coefficient was 1.1×10 -6 / ℃ is a more appropriate modulus.

[0080] Example 3

[0081] A heat-resistant coating composition is prepared from the following components in parts by weight:

[0082] 13.5g of rutile titanium dioxide, 12g of hollow glass microspheres, 3g of rock fiber, 1.5g of zircon sand, 5g of hexatitanate whiskers, 35g of sodium silicate and potassium fluorosilicate shown in Table 3; sodium silicate was prepared into a 35wt% aqueous solution; the surface drying time, coating curing time and temperature after calcination for 5min of Example 3 are shown in the following table: The coating of Example 3 after calcination for 5min Figure 1 shown.

[0083] Table 3 Formulation and partial heat resistance properties of the heat-resistant coating composition of Example 3

[0084]

[0085] The preparation method of the heat-resistant coating composition comprises the following steps:

[0086] 1) Mix rutile titanium dioxide, hollow glass microspheres, rock fiber and zircon sand evenly, add a 35wt% film-forming agent aqueous solution, and stir at high speed;

[0087] 2) adding 20 mL of water to potassium fluorosilicate to prepare an aqueous solution, adding the potassium fluorosilicate aqueous solution to the material in step 1), and adding hexatitanate whiskers while stirring at high speed within 5 minutes to obtain a light gray colloid;

[0088] 3) Add water to the system and adjust the viscosity to 70-90 seconds for coating four cups;

[0089] 4) Apply the coating three times on a 100×100×10mm ordinary carbon steel plate, remove oil and rust, and dry at 120°C to a film thickness of 120μm.

[0090] Depend on Figure 1 It can be seen that in Examples 3a-3e, after calcination for 5 minutes, the temperature difference between the two sides of the test piece obtained in Example 3e is the largest. From Table 3, the amount of potassium fluorosilicate as a curing agent is reduced, the surface drying time of the coating is extended to a certain extent, the curing time of the coating is greatly increased, and the temperature drops sharply after calcination for 5 minutes. It can be seen from the above table that when the amount of potassium fluorosilicate is 1.16-2.3, the coating can achieve a better thermal insulation effect on the basis of having a more suitable coating curing time.

[0091] Example 4

[0092] A heat-resistant coating composition is prepared from the following components in parts by weight:

[0093] 13.5g of rutile titanium dioxide, 12g of hollow glass microspheres, 3g of rock fiber, 1.5g of zircon sand, 5g of hexatitanate whiskers, 35g of sodium silicate and 1.16g of potassium fluorosilicate; sodium silicate is prepared into a 35wt% aqueous solution.

[0094] The preparation method of the heat-resistant coating composition comprises the following steps:

[0095] 1) Mix rutile titanium dioxide, hollow glass microspheres, rock fiber and zircon sand evenly, add a 35wt% film-forming agent aqueous solution, and stir at high speed;

[0096] 2) adding 20 mL of water to potassium fluorosilicate to prepare an aqueous solution, adding the potassium fluorosilicate aqueous solution to the material in step 1), and adding hexatitanate whiskers while stirring at high speed within 5 minutes to obtain a light gray colloid;

[0097] 3) Add water to the system and adjust the viscosity to 70-90 seconds for coating four cups;

[0098] 4) Apply the coating three times on a 100×100×10mm ordinary carbon steel plate and apply it to the corresponding film thickness at a drying temperature of 120°C.

[0099] Table 4 Film thickness and partial heat resistance of the heat-resistant coating composition of Example 4

[0100]

[0101] It can be seen from Table 4 that when the drying temperature is 120°C, as the film thickness of the test piece increases, the baking temperature difference reaches a peak inflection point at 120 μm, and no obvious increase is observed thereafter.

[0102] Example 5

[0103] A heat-resistant coating composition is prepared from the following components in parts by weight:

[0104] 13.5g of rutile titanium dioxide, 12g of hollow glass microspheres, 3g of rock fiber, 1.5g of zircon sand, 5g of hexatitanate whiskers, 35g of sodium silicate and 1.16g of potassium fluorosilicate; sodium silicate is prepared into a 35wt% aqueous solution.

[0105] The preparation method of the heat-resistant coating composition comprises the following steps:

[0106] 1) Mix rutile titanium dioxide, hollow glass microspheres, rock fiber and zircon sand evenly, add a 35wt% film-forming agent aqueous solution, and stir at high speed;

[0107] 2) adding 20 mL of water to potassium fluorosilicate to prepare an aqueous solution, adding the potassium fluorosilicate aqueous solution to the material in step 1), and adding hexatitanate whiskers while stirring at high speed within 5 minutes to obtain a light gray colloid;

[0108] 3) Add water to the system and adjust the viscosity to 70-90 seconds for coating four cups;

[0109] 4) Apply the coating three times on a 100×100×10mm ordinary carbon steel plate, and according to the drying temperature and drying time recorded in Table 5, the coating film thickness is 100μm.

[0110] Table 5 Film thickness and partial heat resistance of the heat-resistant coating composition of Example 5

[0111]

[0112] From the effects of drying temperature and drying time on heat resistance parameters in Table 5, it can be seen that when the drying temperature is 120℃ and the drying time is 2 hours, the baking temperature difference can reach 1058℃, and the thermal expansion coefficient can reach 1.6×10 -6 / ℃. Because the drying temperature and time affect the surface state and crystal form of the coating, they have a great influence on the heat resistance and thermal expansion of the coating.

[0113] Example 6

[0114] A heat-resistant coating composition is prepared from the following components in parts by weight:

[0115] 13.5g of rutile titanium dioxide, 12g of hollow glass microspheres, 3g of rock fiber, 1.5g of zircon sand, 5g of hexatitanate whiskers, 35g of sodium silicate and 1.16g of potassium fluorosilicate; sodium silicate is prepared into a 35wt% aqueous solution.

[0116] The preparation method of the heat-resistant coating composition comprises the following steps:

[0117] 1) Mix rutile titanium dioxide, hollow glass microspheres, rock fiber and zircon sand evenly, add a 35wt% film-forming agent aqueous solution, and stir at high speed;

[0118] 2) adding 20 mL of water to potassium fluorosilicate to prepare an aqueous solution, adding the potassium fluorosilicate aqueous solution to the material in step 1), and adding hexatitanate whiskers while stirring at high speed within 5 minutes to obtain a light gray colloid;

[0119] 3) Add water to the system and adjust the viscosity to 70-90 seconds for coating four cups;

[0120] 4) According to the pretreatment method recorded in Table 6, a 100×100×10 mm ordinary carbon steel plate was pretreated by brushing three times, drying at 120°C and drying for 2 hours, and the coating film thickness was 120 μm.

[0121] Table 6 Effect of steel plate pretreatment on heat resistance parameters

[0122]

[0123] It can be seen from the above table that before coating, the carbon steel plate sample is first degreased and derusted, which can effectively improve the adhesion of the test piece coating to the steel plate. The performance of the obtained test piece is greatly improved, and the baking temperature difference can reach 1058℃.

[0124] It can be seen from the above embodiments that rutile titanium dioxide as fine aggregate is the main heat-resistant component, and ball-milling to less than 200nm can form a film layer with uniform texture and good film-forming effect. The hollow glass microbeads used form physical heat-insulating channels in the coating, further hindering the spread of heat; the rock fiber used as rock fiber provides better toughness and hardness support for the coating, thereby making the texture of the coating firmer; the zircon sand used has a smaller thermal expansion coefficient, so that the coating maintains a smaller deformation under long-term thermal radiation conditions. In other words, the composition and ratio of the entire fine aggregate synergistically determine the better advantages of the heat-resistant coating composition over other heat-resistant coating compositions in terms of basic insulation, strength, and expansion coefficient parameters.

[0125] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A heat-resistant coating composition, characterized in that: The invention is made of the following components by weight: 30-35 parts of fine aggregate, 2-10 parts of potassium hexatitanate whiskers, 30-40 parts of film formers and 1-5 parts of curing agents; the film formers are sodium silicate; the curing agents are potassium fluorosilicate; the sodium silicate is prepared into a 30-40wt% aqueous solution; the modulus of the film former is 3-3.5; The fine aggregate is made of the following components by weight: 35-45% hollow glass microspheres, 5-20% rock fiber, 2-10% zircon sand and 100% rutile titanium dioxide; The particle size of the rutile titanium dioxide is less than 200 nm, and the particle size of the hollow glass microspheres is less than 100 μm; The preparation method of the heat-resistant coating composition comprises the following steps: 1) Mix fine aggregates evenly, add the aqueous solution of sodium silicate, and stir at high speed; 2) adding an aqueous solution of a curing agent to the material of step 1), and adding potassium hexatitanate whiskers while stirring at high speed; 3) Add water to adjust the viscosity to 70-90 seconds for coating four cups; 4) Apply to the carrier and dry at 110-130℃ to a film thickness of 80-120μm.

2. The heat-resistant coating composition according to claim 1, characterized in that: The fine aggregate is made of the following components in weight percent: 35-40% of hollow glass microspheres, 10-15% of rock fibers, 4-6% of zircon sand and 100% of rutile titanium dioxide.

3. The heat-resistant coating composition according to claim 1, characterized in that: The invention is prepared from the following components by weight: 30 parts of fine aggregate, 5 parts of potassium hexatitanate whiskers, 35 parts of film formers and 1.5-1.75 parts of potassium fluorosilicate; the modulus of the film former is 3, and the film former is prepared into a 35wt% sodium silicate aqueous solution.

4. The heat-resistant coating composition according to claim 1, characterized in that: In step 4), the film is dried at 120°C to a film thickness of 100-120 μm.

5. The heat-resistant coating composition according to claim 1, characterized in that: In step 1), the speed of high-speed stirring is 500 r / min, and the stirring time is greater than 30 min.

6. The heat-resistant coating composition according to claim 1, characterized in that: In step 4), the carrier is a common carbon steel plate, which is first degreased and derusted before coating.

Citation Information

Patent Citations

  • High temperature resistant heat insulation coating and preparation method thereof

    CN101531864A

  • Double-coated hollow glass microbead heat-insulated coating and preparation method thereof

    CN102391754A